Peningkatan Hasil Belajar Menggunakan Pendekatan TaRL pada Materi Kegiatan Ekonomi Jual Beli di Sekolah Dasar - Endah Nur Aini; Fauzatul Ma’rufah Rohmanurmeta; Muhammad Nasrulloh (Lembaga Pengembangan Kinerja Dosen, 2024)
Based on the aim of improving student learning outcomes, this classroom action research evaluates the effectiveness of using the Teaching at the Right Level (TaRL) approach. The TaRL approach ensures that learning is differentiated to meet the needs of diverse students. This research aims to assess how this integrated approach affects overall learning success. PTK was carried out in class IV of SDN 01 Kanigoro with a total of 11 students in July 2023 with 2 cycles. Implementation of each cycle is carried out starting from problem diagnosis, design action, event observation, evaluation and reflection. Data collection techniques use observation, tests and documentation. The research results show an increase in student learning outcomes achieving the expected results. The results of research in cycle I showed that the learning outcomes of 7 students (63.63%) achieved learning completeness. In cycle II, there was a more significant increase, where 11 students (90.90%) achieved learning completion. Apart from that, the average result also increased significantly from 64.27 in the pre-cycle stage to 80.2 in cycle I and 88.1 in cycle II. Thus, this research provides evidence that the application of the TaRL approach is effective in improving student learning outcomes in the science and sciences subject material on buying and selling economic activities.